Faktor-Faktor Yang Mempengaruhi Motivasi Belajar Mahasiswa Tingkat Ii Akademi Keperawatan Dirgahayu Samarinda - Ns. Yani (DEDIKASI : Jurnal Ilmiah Sosial, Hukum, Budaya, 2016)
This studyaims to describethe effect of motivation on students' academic achiev ementlevelIIat Nursing Academy Dirgahayu Samarinda.This study is quantitative with associative purpose, namely to explain causal relationships between variable ‘X’and variable ‘Y’. The variables of the study is the motivation (X) as the independent variable and student achievement (Y) as the dependent variable.To measure the variables of this study used a questionnaire to the respondent based on the indicator predetermined. The population of this study were all students of Nursing Academy Dirgahayu registered at BAAK and be active in lecturing starts from class of 2009 to 2012. Of this population, taken as many as 157 respondents as sampling study. The data analysis technique used is the technique of descriptive statistical analysis and inferential analysis technique that aims to assess the research variablesThe results showed that: (1) Student of Nursing Academy Dirgahayu at level 2 who have high creativity as much as 21.51%, high enough creativity 49.42%, less high creativity 25,58% and low creativity 3.49%. Thus the students of Nursing Academy Dirgahayu at level 2tends to be quite high creativity. (2) Student of Nursing Academy Dirgahayu at level 2 who have a visual learning style as much as 44.19%, kinesthetic learning style 24.42% and auditory learning styles 30.82%. (3) Student of Nursing Academy Dirgahayu at level 2 who have medical-surgical learning achievement as very competent 35.47%, quite competent 37.21%, a competent 18.60%, and less competent 8.72%. Thus the medical-surgical student learning achievement of Nursing Academy Dirgahayu at level 2 is competent enough. (4) There is a positive and significant relationship between creativity and learning styles with medical-surgical student learning achievement (correlation coefficient of 0.906 and the value of determination coefficient of 0.820), or variance of learning achievement in medical-surgical is 82% can be explained by creativityvariable and learning stylevariable. (5) There is a positive and significant relationship between creativity and academic achievement surgical medical students (a correlation coefficient of 0.900 and the value of determination coefficient of 0.809), or learning achievement in medical-surgical variance of 80.9% can be explained by the variable creativity. (6) There is a positive and significant relationship between learning styles and academic achievement surgical medical students (a correlation coefficient of 0.393 and the value of determination coefficient of 0.154), or learning achievement in medical-surgical variance of 15.4% can be explained by the creativity variable and learning stylesvariable. (7) There is no difference significantly between students who have a visual-auditory learning style, kinesthetic visual, and kinesthetic auditory learning achievement in surgical medical students.